Mode-Matching Analysis for Sound Propagation in a Cylindrical Duct with a Partial Lining - TİRYAKİOĞLU, BURHAN (My University, 2023)
Abstract: A mode-matching analysis of infinite cylindrical duct with a partial absorbing internal surface is considered. The solution for the field terms are determined in form of eigenmodes which are matched across the boundary of each junction discontinuity. Numerical results are performed to show the influence of the different parameters such as waveguide radius, length of the lined part and acoustic absorbing lining on the propagation phenomenon. The method is also compared with the Wiener–Hopf technique which is more difficult to implement and very good corroboration is observed.
Keywords: Fizik; Elektromanyetizma, Akustik, Isı Transferi, Klasik Mekanik ve Akışkanlar Dinamiği; Akustik; Temel Bilimler; Physics; Electromagnetism, Acoustics, Heat Transfer, Classical Mechanics and Fluid Dynamics; Acoustics; Natural Sciences; Temel Bilimler (SCI); AKUSTİK; Natural Sciences (SCI); PHYSICS; ACOUSTICS; Akustik ve Ultrasonik; Fizik Bilimleri; Acoustics and Ultrasonics; Physical Sciences; absorbent lining; acoustics; circular duct; mode-matching technique; wave propagation